Al-Quran Memorizing Training Using 2T+1M Method for Student with Visual Disability Through the Zoom Application - Azizah, Nur; Prasetyo, Adhit Cahyo; Azis, Abdul; Munggaran, Wulan Syakinah; Asih, Neng Sri Sinta (JASSI ANAKKU, 2021)
Allah has guaranteed convenience for anyone who wants to memorize the Qur'an, including students with visual disabilities. However, it is necessary to have the right method and make it easier for the student with visual disabilities to memorize the Quran. This study aims to provide an overview of the training to memorize the Quran for the student with a visual disability using the 2T+1M method. This research uses the descriptive qualitative method. Data collection techniques using observation and interview with mother of a student with visual disability. The data analysis technique uses the Miles and Huberman model analysis which has 3 stages, namely data reduction, data presentation, and conclusion. Al-Quran memorization training is carried out by volunteers from the SIEP (Social Inclusive Education Project) community through the Zoom Meeting application. The chapter name is An-Naziaat verses 1 to 46. The training was carried out for 9 meetings by applying the 2T+1M method, namely Talqin or Tasmi, Tikrar, and Murajaah. During the Quran memorizing training using the 2T+1M method, the student with a visual disability with the initial E was able to listen to verse by verse, was able to repeat the reading of the Quran with a calm attitude, was able to repeat the reading of each verse with correct pronunciation and tajwid rules, and able to maintain the memorization that has been memorized previously.